Propuesta de mejoramiento de las condiciones de operación y servicio en establecimientos gastronómicos del sector Barranquillita municipio de Madrid Cundinamarca - Mora Duarte, Edna Katherine; Rojas Acosta, Luisa Fernanda (Universidad Antonio Nariño, 2023)
The main objective of this document is to facilitate knowledge of the adequate process of operation and service in the restaurants of a sector known as Barranquillita located in the Municipality of Madrid Cundinamarca, which carry out their activities in conditions not suitable for providing a correct food service to the community in which not only its inhabitants are affected, but also the people who visit it.